The Emotional-Psyc hological Consequences of Infertility and Its Treatment - Nahrin, Noor E; Ashraf, Fatema; Nessa, Khairun; Alfazzaman, Md; Anwary, Shaheen Ara; Abedin, Syed AM Asfarul; Rahman, MM Mafizur (Medicine Today, 2017)
Infertility is a major public health concern accounting for 10%-15% all over the world. In Bangladesh about 24.51 million patients receive infertility advice or treatment. The emotional consequences of an infertility diagnosis can be devastating. One study in Taiwan diagnosed anxiety in 23% and major depression in 17% of the women seeking assisted reproductive infertility treatment. The aim of this case presentation is to addressing the psychological consequences of infertility and its treatment. The findings of this case study are: 1. Understanding the reactions of infertility (mental engagement; psychological turmoil). 2. Consequences of therapy process (reduced self-esteem; feelings of failure, economic burden). 3. Emotional-affective reactions to therapy process (fear, anxiety and worry; fatigue and helplessness; grief and depression; hopelessness). This case study revealed that infertile women seeking treatment face several psychological-emotional problems with devastating effects on the mental health and well-being of the infertile individuals and couples, while the infertility is often treated as a biomedical issue with less attention on the mental-emotional, social and cultural aspects. Medicine Today 2017 Vol.29(1): 42-44